A myriad of fat - Kodiatte, Abraham A.; Jacob, Jubbin J. (International Journal of Advances in Medicine, 2018)
Hypertriglyceridemia is a familiar issue a physician and his patients face. Writing a prescription for the same may be effortless, but without a thorough evaluation, we may miss out on a number of concealed diseases. Treating the underling secondary disease, avoids an unnecessary pill burden, eventually decreasing healthcare costs also. Unearthing prevalent diseases like diabetes mellitus (DM) is rewarding in its own way and pays dividends multifold. The physician must be aware that secondary causes of hypertriglyceridemia manifesting as lipemia can commonly be seen in disorders like obesity, primary hypothyroidism and DM. The studied patient presented to us obviously shaken with a long history of weight gain and lipemia during a blood draw. She turned out to have the commonest risk factors for hypertriglyceridemia - Obesity, hypothyroidism and DM causing the alarming lipemia. It was an oddly interesting presenting symptom of hypertriglyceridemia, obesity, hypothyroidism and DM which resulted in an appropriate and prompt management of her underlying diseases.